The Patterns and The Motives of the Iraqi Public’s Exposure to Advertisements in Satellite Channels: A Field Study of Baghdad Public’s Exposure to Al-Sumaria channel for the Period from 1/1/2011 until 1/4/2011 - Al-Musawi, Kareem Meshet Zelef (Al-Adab Journal, 2020)
The study of the public is very important for planning and implementing any advertising activity, as it requires scientific knowledge of the factors determining the public’s behavior, including motivations, attitudes, personal inclinations, customs, and traditions. It is also important for formulating a declaration that corresponds to the trends, desires, goals, and motivations of the public as a positive participant in the advertising communication process. This research tries to mix more than one goal in its study as it relates to communication researches on one hand dealing with theoretical aspects in this field, and on the other hand, it belongs to impact researches which deal with the importance of the role that satellite channels play in the economic aspect of society (the opportunities of buying and selling), as well as the impact of the trends in the consumption pattern. Thus, they complement other impacts in influencing the behavior of the public. Consequently, this research belongs to investigative researches as the main motives are to achieve the objective interaction between the parts of the communication process. To achieve these goals, the researcher relied on the analysis method in his study by designing a questionnaire form according to the results of an initial survey study conducted on a limited random sample, leading to appropriate practical methods. The second chapter was divided into three sections. The first section discussed the concept of exposure and advertising, the second section discussed the characteristics of advertising in satellite channels, and the third section devoted to social and economic impacts of advertisements on public. The third chapter devoted to the field study, whereby the researcher prepared a number of scientific tables and data, explaining them scientifically, giving samples of these advertisements, then coming up with scientific conclusions based on the problem, the goals of the research, then to a number of recommendations that the researcher considers them appropriate to the problem.